Evaluation of the use of probiotic acid lactic bacteria in the development of chicken hamburger - Bomdespacho, L. Q. [UNESP]; Cavallini, D. C.U. [UNESP]; Zavarizi, A. C.M. [UNESP]; Pinto, R. A. [UNESP]; Rossi, E. A. [UNESP] (My University, 2014)
The objective of this study was to investigate the effect of fermentation with Lactobacillus acidophilus CRL 1014 on the physicochemical, microbiological and sensory characteristics of a hamburger product like processed with chicken meat and okara flour, with reduction of curing salts. A mixture of ingredients containing 90% chicken meat and 10% okara flour was subjected to the following treatments: F1: fermented with Lactobacillus acidophilus; F2:75 mg nitrite/kg and fermented with Lactobacillus acidophilus; F3: 150 mg nitrite/kg and unfermented. The quality of the hamburgers was assessed by physical and chemical analysis (pH, cooking yield and shrinkage), chemical composition, microbiological tests (Salmonella spp., count of sulphite-reducing clostridia, staphylococos coagulase-positive, total coliforms and Escherichia coli) and sensory analysis (sensory acceptance and purchase intent). During the first six days of fermentation, there was a decrease in pH from approximately 6.33 to 5.10. All the samples showed the same chemical composition (p < 0.05). The fermentation process was observed to inhibit the multiplication of microorganisms of several groups: coagulase-positive staphylococci, sulphite-reducing clostridia, Salmonella spp. and E. coli. The different hamburgers formulations showed high scores for all the sensory attributes evaluated, without differing from each other (p < 0.05). The results showed that the use of L. acidophilus CRL 1014 enabled the production of a safe product, with good physicochemical and sensory characteristics, in the absence of curing salts. © 2008 IFRJ.
Keywords: Curing salts; Lactobacillus acidophilus; Meat products; Okara